The Occurrence of Paraffin and Other Petroleum Waxes in the Marine Environment: A Review of the Current Legislative Framework and Shipping Operational Practices - Suaria, Giuseppe; Aliani, Stefano; Merlino, Silvia; Abbate, Marinella (Frontiers in Marine Science, 2018)
Among the various materials that make up marine debris, lumps of petroleum waxes such as paraffin and microcrystalline wax, are regularly found on beaches worldwide, although not included in the current definition of marine litter. Ingestion by marine organisms is occasionally documented in the scientific literature and mass beaching events are frequently reported along the European coasts, with obvious detrimental consequences to the local communities that have to manage the clean-up and disposal of this substance. According to Annex II of the MARPOL regulation, petroleum waxes are classified as “high viscosity, solidifying and persistent floating products”, whose discharge at sea of tank-washing residues is strictly regulated, but currently permitted within certain limits. Starting from the description of a large stranding event occurred along the Italian coasts in 2017, we review the existing knowledge and regulatory framework and urge the relevant authorities to address this issue, showing that wax pollution is creating evident damages to the European coastal municipalities. Pending further investigations on the potential hazard that this kind of pollution is posing to marine ecosystems, we suggest a careful and more stringent revision of the policies regulating discharges of these products at sea.